Deployment of Taguchi method for optimization of heat treatment process parameters in raw unclean Edible Bird’s nest - Tay, Guo Xuan; Mas Nordiana Rusli,; Khairul Anuar Mohd Ali,; Zainol Mustafa, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Heat treatment process as one of the Critical Control Points (CCP) of raw unclean edible bird’s nest processing. Main objective of the study was on the determination of optimal combination for the processing. The treatments were the combinations from orthogonal array and signal to noise ratio from Taguchi method with several control variables of conveyor belt speed (0.5, 1.0, 1.5 rpm), temperature of steam shrink tunnel (80, 90, 100 ℃) and temperature sensors allocation (Base, Body, Head) were applied in heat treatment process. L9 (33 ) orthogonal array was adopted in the study where 18 runs were performed with two replications. For this case study, “larger-the-better” approach was selected with the aim to minimize heat penetration time. Results displayed that the optimum condition for heat penetration duration was 11 seconds, where the conveyor belt speed, steam shrink tunnel temperature and temperature sensor allocation were 0.5 rpm, 90℃ and head position respectively. Conveyor belt speed was the highest factor that affected heat penetration duration of raw unclean edible bird’s nest.